The outside thing : modernist lesbian romance - Roche, Hannah, 1985- (Gender and culture., 2019)
"The Outside Thing argues for the significance of literary and affective romance in shaping the work of three major modern lesbian writers: Gertrude Stein, Radclyffe Hall, and Djuna Barnes"--